RADIOLOGY TEACHING FILES IN RESIDENT RADIOLOGY EDUCATION-ASSESSMENT OF THEIR ROLE AND NE - Nikolova, Sonja (My University, 2018)
The radiology imaging technology evolution has the predominantplace among all affiliated sciences. There is an urgent need for knowledge and skills development of our radiology residents. Thus developing critical thinking skills of residents is imperative in an era ofrapidlyadvancing technology.A radiology teaching file is a collection of cases with teaching benefit. Given the wide range of teaching files available, wecomprised an institutional survey with a list of relevant queries to understand the need for implementation, utilization and preferences of teaching files among residents.The survey included and was completed by 40 attending residents at our Institution.Teaching files were appointed to one of three categories: personal, shared, and public teaching files. Fifty percent of residents kept a personal teaching file using a variety of media, and 45% used a shared teaching file. Most popular public teaching files were those requiring paid subscriptions. The quality residents valued most, provided efficient querying of cases, simulated basic PACS functionality, enabled self-directed learning, and facilitated case submissions. There is a tendency toward exploitingelectronic media for teaching files.
Keywords: teaching file; resident; education; radiology